The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/prot.22165
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the outer membrane protein OprF of Pseudomonas aeruginosa in a lipopolysaccharide membrane by computer simulation

Abstract: The N-terminal domain of outer membrane protein OprF of Pseudomonas aeruginosa forms a membrane spanning eight-stranded anti-parallel β-barrel domain that folds into a membrane channel with low conductance. The structure of this protein has been modeled after the crystal structure of the homologous protein OmpA of Escherichia coli. A number of molecular dynamics simulations have been carried out for the homology modeled structure of OprF in an explicit molecular model for the rough lipopolysaccharide (LPS) out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 50 publications
(83 reference statements)
4
51
1
Order By: Relevance
“…To better understand the local effects of the OM on embedded proteins, we developed an OM model suitable for MD simulations. The hydrophobic thickness and lateral diffusion rates of LPS in this OM model correspond reasonably well with previous simulations and experiments (7,11,38,39,42); however, the area per lipid/ LPS is~5-10% higher than that of a similar E. coli OM model (39), suggesting necessary changes for future iterations of our model. Finally, we carried out simulations of an OM transporter, BtuB, in a symmetric phospholipid bilayer and our model OM to characterize novel proteinmembrane interactions in the native environment.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…To better understand the local effects of the OM on embedded proteins, we developed an OM model suitable for MD simulations. The hydrophobic thickness and lateral diffusion rates of LPS in this OM model correspond reasonably well with previous simulations and experiments (7,11,38,39,42); however, the area per lipid/ LPS is~5-10% higher than that of a similar E. coli OM model (39), suggesting necessary changes for future iterations of our model. Finally, we carried out simulations of an OM transporter, BtuB, in a symmetric phospholipid bilayer and our model OM to characterize novel proteinmembrane interactions in the native environment.…”
Section: Discussionsupporting
confidence: 85%
“…The mean-square displacement was also determined for the LPS center of mass, which resulted in nearly identical diffusion values (data not shown). Root mean-square fluctuation (RMSF) values were calculated only for the C a atom of each amino acid (42) to remove rotamer conformation bias. A full summary of the aforementioned values for each system can be found in Table S2.…”
Section: Discussionmentioning
confidence: 99%
“…Both OprF and OprD have β-barrel structures and are embedded in the outer cell membrane, which is comprised of lipopolysaccharide (LPS) (Biswas et al 2007;Staatsuma and Soares 2009). These proteins form channels for transporting substrates through the outer membrane and have considerably similar structures, properties, and functions.…”
Section: Identification Of Proteins With N-terminal Amino Acid Sequenmentioning
confidence: 99%
“…On the issue of convergence, 5 ns is a short timescale in the biological world; membrane equilibration may require 20-40 ns of simulation time. However, we draw confidence from prior studies of 5-10 ns timescale that were shown to predict the general dynamics of studied protein [23,73]. Our subject protein has exhibited structural adaptation to the thinner DMPE membrane as a consequence of hydrophobic mismatch.…”
Section: Discussionmentioning
confidence: 52%